Review of Histopathological Diagnoses of One Year Appendectomy Specimens in Sulaimani City - yaseen, Hadeel; khudaier, Hassanain; Ibrahim, ali (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To review and see the pattern of histopathological diagnoses of one year appendectomy specimens.Methodology: This retrospective study was carried in Sulaimani Teaching Hospital over the period of one year (from 1stof January to 31st of December 2009). All pathological reports were reviewed retrospectively for patient’s age, sex,histopathological diagnosis and operative findings (if present). Histopathological diagnoses then were classified intoeither positive or negative for acute inflammation. Any associated findings or any surgical specimen removed with theappendix was recorded. The obtained data were analyzed by using the statistical package social sciences (SPSS) version19; with Chi square to test for significance between data.Results: Hospital pathological reports of 2052 appendectomy cases were reviewed, (47.12%) were males and (52.88%)were females. 61.9% of all appendectomy cases were positive for acute inflammation (32.9% had acute appendicitis;26.1 % had acute suppurative appendicitis , and 4.5% had gangrenous appendicitis), while 38.1% were negative (28.5 %had reactive follicular hyperplasia, 6.2% were normal, and 0.2% had carcinoid tumors). Negative for acuteinflammation cases were generally significantly more common in females e.g. periappendicitis, Reactive FollicularHyperplesia and carcinoid tumor but eosinophilic appendicitis cases like acute appendicitis were more common inmales. Normal appendixes versus Reactive Follicular Hyperplesia (without associated appendicitis) are two entities thatintermingle. Chronic appendicitis is controversial entity. Out of 20 cases with Entrobius vermicularis (95%) cases wereassociated with reactive follicular hyperplasia and it shows non significant association with acute appendicitis.Recommendation: We recommend that the pathologists must be strict to histological criteria for each pathologicalentity before the diagnosis.